Review on facial expression modeling - Noor Adibah Najihah Mat Noor; Norhaida Mohd Suaib (Bulletin of Electrical Engineering and Informatics, 2022)
Facial modeling has been an ongoing research for many years and still shows research trend due to its relevance to current technology. Many applications incorporate facial expression modeling with the help of facial tracking, facial animation and facial recognition. The existing performance of the modeling method faces the challenges to perform well due to many factors. Currently, the use of 2D images and videos as inputs for modeling process are gaining popularity. However, current technologies and development had extended the trends towards acquiring 3D human data. This paper provides an overview on variety of modeling techniques based on human facial model that can lead to future research.